Contribuições para o estudo de aerogeradores em operação coordenada com STATCOM - Lucas, Marlos Diógenes (2015)
The constant increase in energy demand of a country is always the target of concern for system operators. This implies directly in increasing degree of requirement of the new grid procedures. Among other types of requirement, the ONS (National Electricity System Operator), requests, for example that the tension is controlled by contractor requestor is always controlled between 0.95 and 1.05 p.u.. When there are in the system, wind generation plants based on doubly fed induction machine, this concern is even greater. This is because this type of machine, has its stator connected directly to the network, and in turn more sensitive to voltage fluctuations. Knowing this, in recent years the power electronics is being increasingly present in the electricity sector to mitigate these failures, the example of Static Synchronous Compensator, the STATCOM, that through the management of reactive power, can improve and the point until oscillation effects of annular tension. Targeting an application similar to this, this work brings an idea of STATCOM operating in conjunction with wind farms on serviceability of the desired bar voltage. It was decided to base the study on existing scenario in northeastern Brazil because this way, you can get a sense of the real effects of a STATCOM can bring, positively, to the system. This paper presents a technique for STATCOM sizing as well as general discussions about possible disadvantages of this application. In addition, is used two softwares for preparation of results: MatLab, which through scripts calculates all points of interest for analysis; and ANAREDE, for verification and comparison of the results obtained through the first software .